Penerapan Model Seemingly Unrealated Regression (SUR) Spasial pada Tingkat Kasus Kriminalitas di Provinsi Sulawesi Selatan - Rasyid, Adiatma; Kasse, Irwan; Sauddin, Adnan (Jurnal MSA (Matematika dan Statistika serta Aplikasinya), 2021)
This research conducted discusses the crime rate in South Sulawesi Province. There are several main factors that can lead to crime, especially in South Sulawesi Province. This research was conducted to see the Spatial Seemingly Unrealated Regression SUR) model at the crime rate in South Sulawesi Province, but there are assumptions that do not meet the SUR Spatial Analysis, so the model obtained is limited to the Spatial Autoregressive (SAR) and Spatial Eror Model (SEM). The SAR model obtained shows that the population, the number of poor people, and the GDP per capita have a positive and significant effect on the risk of the population being affected by crime. The SEM model obtained shows a positive and significant effect between the population, the number of unemployed has a negative and significant effect on the risk of the population being exposed to crime.